Determination of Pollution on Photovoltaic Panels by Image Processing - Disli, Firat; Gedikpinar, Mehmet; Sengur, Abdulkadir (Ieee, 2018)
The increase in energy demand every passing day necessitates a shift towards alternative energy sources. Photovoltaic (PV) is one of the alternative energy methods. The efficiency of PV systems is significantly affected by environmental factors such as temperature and panel pollution. It is important to identify adverse factors in improving the performance of PV systems. In this study, the determination of the contamination on the PV panels by using image processing techniques has been achieved. In the PV system, two identical panels were used, one of which was left to be contaminated naturally and the other was kept clean to be used for reference values. The calculations made from the obtained electrical data and the image processing results are shown separately with tables and graphs and the relation between them is evaluated.
Fotovoltaik Panellerin Kirliliginin Görüntü Isleme ile Belirlenmesi
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 28-30, 2018 -- Inonu Univ, Malatya, TURKEY
Keywords: Photovoltaic system; digital image processing; panel pollution